126 White-Eyed Blowout Fracture in The Paediatric Patient Thought to Be A Head Injury – A Missed Diagnosis. (4th May 2021) - Dattani, A; Chauhan, A; Dave, R; Messahel, A
Abstract: White eyed blowout fracture or 'trapdoor fracture' is an orbital floor injury caused by blunt force trauma directly to the orbit causing ocular muscle entrapment between fractured bones of the floor of the orbit. It is most commonly encountered in the paediatric patient population and presents acutely with little to no periorbital signs of injury. This serious diagnosis is frequently missed at initial presentation due to a lack of obvious soft tissue pathology, termed "White Eyed" blow out fracture. It is frequently misdiagnosed as a head injury due to presenting nausea and vomiting and failure to examine eye movements. The authors present a case of a 15-year-old male who suffered blunt force trauma to the orbit and a white eyed blowout fracture ensued. This was not identified in the emergency department and the patient consequently suffered permanent motility deficit of the globe. We outline recommendations for emergency department practitioners to help identify such presentations and see their timely surgical management.